Motor learning and control concepts and applications - Magill, Richard A.; Anderson, David I. (McGraw Hill, 2021)
This twelfth edition primarily updates the previous edition by adding more recent research and interpretations of the concepts and theoretical views associated with those concepts that were in the eleventh edition. Similar to the previous editions this new edition continues its two most distinctive features as an introductory motor learning and control textbook: its overall approach to the study of motor learning and control and the organization of the implementation of that approach. In every edition of this book, the overall approach has been the presentation of motor learning and control "concepts" to identify the common theme of each chapter